2018
DOI: 10.1007/s11284-018-1617-x
|View full text |Cite
|
Sign up to set email alerts
|

Short, medium and long‐term effects of density on the demographic traits of a threatened newt

Abstract: Mediterranean streams undergo seasonal reductions in water availability that may affect amphibian demography due to habitat loss and the concentration of individuals in the shrinking aquatic habitats. However, there are few empirical examples of how increased population density experienced by larval stages produces long‐term effects on growth and fitness at postmetamorphic stages. We tested the effect of four different larval densities on the demography and growth of the endangered stream‐dwelling newt Euproct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Indeed, newts use aquatic habitats during the breeding period and adopt a terrestrial lifestyle during the rest of the year, consuming invertebrates that comprise a large part of their diet (Joly & Giacoma, ; Schabetsberger & Jersabek, ; Vignoli, Luiselli, & Bologna, ). Adult body size should be attained mainly during the juvenile phase of life even if the aquatic larval phase is thought also to be responsible for adult growth (Halliday & Verrell, ; Vignoli et al, ). It would be expected, therefore, that different habitat conditions and feeding strategies in aquatic habitats would affect adult body sizes, with body size in artificial water bodies smaller than in natural ones (Nobili & Accordi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, newts use aquatic habitats during the breeding period and adopt a terrestrial lifestyle during the rest of the year, consuming invertebrates that comprise a large part of their diet (Joly & Giacoma, ; Schabetsberger & Jersabek, ; Vignoli, Luiselli, & Bologna, ). Adult body size should be attained mainly during the juvenile phase of life even if the aquatic larval phase is thought also to be responsible for adult growth (Halliday & Verrell, ; Vignoli et al, ). It would be expected, therefore, that different habitat conditions and feeding strategies in aquatic habitats would affect adult body sizes, with body size in artificial water bodies smaller than in natural ones (Nobili & Accordi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Together, our results support a growing number of studies, on a variety of taxa, that have been unable to show that large eggs, with a supposedly unfavorable surface-area-to-volume ratio for gas diffusion, are more susceptible to oxygen limitations during development (Einum et al 2002; Braga Goncalves et al 2015b; Polymeropoulos et al 2016; Rollinson and Rowe 2018). However, the smaller embryo sizes observed in the more densely packed broods of small males may result from constraints in other types of paternal investment, such as nutrient provisioning, as found in burying beetles (Monteith et al 2012), or due to sibling competition, as found in newts (Vignoli et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We represented each population using a simple logistic growth modelNt+1goodbreak=Ntgoodbreak+Nt0.25emrmaxKNtK,reflecting density dependence as hypothesized for this species (Colomer et al, 2014) and observed in other stream‐dwelling newts (Gill, 1979; Petranka & Sih, 1986; Vignoli et al, 2018). We parameterized the model using available evidence for C. arnoldi or for its sister species C. asper (ecologically broadly similar), and formally elicited expert judgement (Table 1).…”
Section: Methodsmentioning
confidence: 99%